Over-indebtedness and poverty: Patterns across household types and policy effects - Sarah Kuypers; Gerline Verbist (National Bank of Belgium, 2022)
Household debt has increased significantly since the second half of the 20th century, making it one of the cornerstones of household financial behaviour. It is, however, necessary to monitor that indebtedness does not spiral out of control, as it can have negative consequences both at the micro and macro level. In this paper, we measure over-indebtedness in the poverty framework, while also taking into account the (potential) leverage by assets. We focus on a case study of Belgium, using data from four waves of the Eurosystem Household Finance and Consumption Survey (HFCS). Our results are relevant both in terms of the levels of over-indebtedness measured as well as from the point of household heterogeneity and policy relevance. While the classical indicators mainly identify those who initially borrow large amounts as over-indebted, our analyses point towards the importance of low disposable income and the ownership of non-mortgage debt in explaining over-indebtedness, poverty and financial vulnerability. We also simulate two potential policy reforms which address these two main risk factors.
Keywords: G51; I32; 330; debt; over-indebtedness; poverty; social policy; Belgium